2017
DOI: 10.1021/acs.est.7b02409
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Mitochondrial Genome on the Relationship of Long-Term Ambient Fine Particle Exposure with Blood DNA Methylation Age

Abstract: The mitochondrial genome has long been implicated in age-related disease, but no studies have examined its role in the relationship of long-term fine particle (PM2.5) exposure and DNA methylation age (DNAm-age) – a novel measure of biological age. In this analysis based on 940 observations between 2000 and 2011 from 552 Normative Aging Study participants, we determined the roles of mitochondrial DNA haplogroup variation and mitochondrial genome abundance in the relationship of PM2.5 with DNAm-age. We used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…For instance, in a cross-sectional study of occupational workers, exposure to particulate matter (PM 10 and PM 1 ) and low-dose benzene was associated with higher mtDNAcn in blood (Hou et al, 2010; Carugno et al, 2012); however, in a repeated measure analysis of exposure to PM or elemental carbon, researchers observed increases in exposure to be associated with lower mtDNAcn (Hou et al, 2013). Similarly, long-term PM 2.5 exposure was associated with decreased mtDNAcn in the Normative Aging Study (Nwanaji-Enwerem et al, 2017). Only two studies have investigated the impact of prenatal exposure to PM on mtDNAcn in cord blood (Janssen et al, 2012; Rosa et al, 2017a); one of these studies also reported results in placenta (Janssen et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, in a cross-sectional study of occupational workers, exposure to particulate matter (PM 10 and PM 1 ) and low-dose benzene was associated with higher mtDNAcn in blood (Hou et al, 2010; Carugno et al, 2012); however, in a repeated measure analysis of exposure to PM or elemental carbon, researchers observed increases in exposure to be associated with lower mtDNAcn (Hou et al, 2013). Similarly, long-term PM 2.5 exposure was associated with decreased mtDNAcn in the Normative Aging Study (Nwanaji-Enwerem et al, 2017). Only two studies have investigated the impact of prenatal exposure to PM on mtDNAcn in cord blood (Janssen et al, 2012; Rosa et al, 2017a); one of these studies also reported results in placenta (Janssen et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…18,[27][28][29] Moreover, DNAm-age has been linked to molecular process involving metabolism, the immune system, cellular aging, and cancer. [30][31][32][33][34][35] We hypothesized that this molecularly informative 66-CpG SI could also be applied to buccal cells. Buccal cells are of particular interest for tobacco smoke exposure, because they are among the few cell types directly exposed to tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of cellular stress seem to affect epigenetic alterations that may lead to deleterious consequences. Exposure to fine particle air pollution affects DNA methylation status in blood cells [ 178 , 179 , 180 , 181 , 182 , 183 ] and placenta [ 184 ]. Cigarette smoking has adverse effects on health and is associated with changes in epigenetic marks.…”
Section: Epigenetics and Agingmentioning
confidence: 99%